An ethnographic study of recreational drug use and identity management among a network of electronic dance music enthusiasts in Perth, Western Australia - Green, Rachael Renee (Curtin University, 2012)
This thesis explores the social contexts and cultural significance of amphetamine-type stimulant (ATS) and alcohol use among a social network of young adults in Perth, Western Australia. The study is positioned by the “normalisation thesis” (Parker et al. 1998), a body of scholarly work proposing that certain “sensible” forms of illicit drug use have become more culturally acceptable or normal among young people in the United Kingdom (UK) population since the 1990s. Academic discussion about cultural processes of normalisation is relevant in the Australian context, where the prevalence of illicit drug use among young adults is comparable to the UK. This thesis develops the work of Sharon Rødner Sznitman (Rødner, 2005, 2006; Rødner Sznitman, 2008), who argued that normalisation researchers have neglected the “micro-politics that drug users might be engaged in when trying to challenge the stigma attached to them” (Rødner Sznitman, 2008, pp.456-457).Ethnographic fieldwork was conducted among ‘scenesters’ – members of a social network that was based primarily on involvement in Perth’s electronic dance music (EDM) ‘scene’. Sixty scenesters were involved in participant observation over 18 months, and a subset of 25 participated in semi-structured, in-depth interviews. This thesis argues that the values associated with particular ATS practices are more nuanced and contested than have been depicted within accounts of normalised drug use. Analysis in this thesis is framed by exploration of the negotiation of dual identities claimed by young adults in this study. These are their self-identification as ‘normal’ within the context of the mainstream community and their simultaneous pursuit of a ‘scenester’ identity and associated partying and illicit drug use. I examine how negotiating the uncertain parameters of these identities, and occupying a position within and between these social fields results in complexities, tensions and nuances in drug practice that were continually negotiated.Two sub-arguments are pursued. First, I argue that the negotiation of drug use that scenesters considered to be acceptable and also pleasurable was complicated by the beliefs and values that were negotiated during the performance of scenester identity. The importance of developing and maintaining status as an authentic scenester contributed to the value placed on maintaining control over one’s physical and emotional state when using drugs. Elaborating on this theme, I begin by exploring the decreased symbolic value of ecstasy use and the preference for moderate and/or private use among scenesters. Scenesters termed its emotional and physical effects ‘gurning’ and considered ecstasy to be a ‘messy’ drug that compromised self-control. Despite the negative associations of ecstasy, it was nonetheless regarded as a fun and pleasurable drug by many. The main argument presented here is that the cultural values attributed to ecstasy use were unsettled and negotiated in flexible ways.I then explore how scenesters reconciled the status of alcohol as a fun and ‘social’ drug but one that was associated with the undesirable experience of loss of control and tiredness. This was achieved through concomitant use of diverted dexamphetamine or ‘dexies’ – a drug readily available in the local landscape. Analysis explores how, while use of dexies was casual, understandings of dexies and the ways scenesters rationalised their use, complicated understandings of drugrelated pleasure and harm. This analysis contributes to nuanced understandings of recreational drug practices.The second sub-argument presented in this thesis is that the stigmatisation of drug use in the community continues to destabilise the expression of recreational drug practice even within a network of recreational illicit drug users. This is initially explored in relation to the practice of smoking crystal methamphetamine (or ‘meth’ smoking). I examine how the status of meth smoking as a recreational drug practice was uncertain and contested within the network. Analysis is contextualised by public discourse emphasising the addictive properties of the drug and its association with personal degradation. I explore two themes. First, negotiation of quasi-private and private forms of use (in ‘meth circles’) illustrates the importance of management of a non-stigmatised identity. Second, inconsistent views about whether meth smoking was social or controlled, and reassessment of involvement by users, exposed the instability of the values associated with recreational style use among scenesters. I argue that the establishment of crystal methamphetamine smoking as a deviant practice within the general community, as well as within the EDM scene, shaped a hidden style of practice that was not easily regulated and was strongly associated with heavy use in the form of ‘benders’.Analysis then explores the micro-level management of recreational drug-using identity over time, particularly in relation to the maintenance of competent and self-managing identities. I argue that scenesters drew on limited, deficit-based social constructions of drug users to derive understandings of what constituted recreational forms of drug use, and therefore boundaries were subjectively interpreted, highly variable and rooted in relational experiences. This is underpinned by uncertainty about the limitations of normalised drug use in relation to the realisation of ‘adult’ identity.This thesis contributes to an increasingly nuanced understanding of the complex and renegotiated aspects of ‘normal’ practice among regular drug users. The shared and processual aspects of recreational drug practices and the renegotiated aspects associated with identity management among young adults are under-developed areas of the normalisation literature that are explored in this study. This study also contributes to the methodological literature in the Australian alcohol and other drugs (AOD) field, which has under-utilised the ethnographic method. Ethnographic analysis of the integration of dexamphetamine into recreational drug practices and the negotiation of crystal methamphetamine smoking among socially integrated drug users also contributes to the current literature. The conclusion of this thesis discusses the implications of the continued stigmatisation of drug users in relation to recreational drug-using young adults.